The influence of the stereotypic forms of activity in mice behaviour in standard behavioural tests - Avimova, Kseniya P.; Sandakov, Dmitry B. (Experimental Biology and Biotechnology, 2021)
Laboratory animals often develop abnormal repetitive (stereotypic) behaviour that can influence both physiology and behavioural test results. Such abnormal behaviours usually develop in suboptimal environment and increase over time. To explore the development of stereotypic forms of activity night home-cage behaviour of laboratory mice was analysed and collated with the behaviour in open field (OFT), hole-board (HBT) and tail suspension (TST) tests twice within 16 weeks. Mice expressed few stereotypies and their duration lessened over time from median 8.2 to 1.0 %. In contrast, grooming behaviour increased significantly from 29.5 to 49.6 %. Home-cage grooming correlated with the latency of locomotion start in OFT and with the immobility time in TST. Intensity and stability of stereotypic activity and grooming influenced the duration of grooming in OFT: the mice with unstable stereotypies groomed more than others, and mice with the lowes home-cage grooming level also groomed in OFT the most. Intensity and stability of night grooming influenced the behaviour in TST: the mice with unstable level of grooming were the most mobile in this test. Abnormal home-cage activity may indicate impaired welfare, and that, in turn, may affect test activity, so researchers need to keep it in mind when planning animal behaviour experiments.